LANGUAGE DEVELOPMENT: EFFECTS OF MONOLINGUAL AND BILINGUAL ENVIRONMENTS - Ancāne, Aiga (Education Reform: Education Content Research and Implementation Problems, 2024)
Speech and language are the basis for a child's successful development, communication and social well-being, as well as the acquisition of academic knowledge and skills. Due to the global trend and the ever-increasing disorders of children's speech and language development, it is necessary to be aware of the influence of a bilingual environment on the child's speech and language development, to clarify the risks and benefits associated with bilingualism, as well as to educate parents and educators about them, so that a child who grows up in a bilingual environment received maximum understanding and, if necessary, support in the process of learning speech and language.